Climate change mitigation through dietary change: a systematic review of empirical and modelling studies on the environmental footprints and health effects of 'sustainable diets'. (22nd December 2020) - Jarmul, Stephanie; Dangour, Alan D; Green, Rosemary; Liew, Zara; Haines, Andy; Scheelbeek, Pauline FD
Abstract: The adoption of healthy diets with low environmental impact has been widely promoted as an important climate change mitigation strategy. Typically, these diets are high in plant-sourced and low in animal-sourced and processed foods. Despite the fact that their environmental impacts vary, they are often referred to as 'sustainable diets'. Here we systematically review the available published evidence on the effect of 'sustainable diets' on environmental footprints and human health. Eight databases (OvidSP-Medline, OvidSP-Embase, EBSCO-GreenFILE, Web of Science Core Collection, Scopus, OvidSP-CAB-Abstracts, OvidSP-AGRIS, and OvidSP-Global Health) were searched to identify literature (published 1999–2019) reporting health effects and environmental footprints of 'sustainable diets'. Available evidence was mapped and pooled analysis was conducted by unique combinations of diet pattern, health and environmental outcome. Eighteen studies (412 measurements) met our inclusion criteria, distinguishing twelve non-mutually exclusive sustainable diet patterns, six environmental outcomes, and seven health outcomes. In 87% of measurements (n = 151) positive health outcomes were reported from 'sustainable diets' (average relative health improvement: 4.09% [95% CI −0.10–8.29]) when comparing 'sustainable diets' to current/baseline consumption patterns. Greenhouse gas emissions associated with 'sustainable diets' were on average 25.8%[95%CI −27.0 to −14.6] lower than current/baseline consumption patterns, with vegan diets reporting the largest reduction in GHG-emissions (−70.3% [95% CI: −90.2 to −50.4]), however, water use was frequently reported to be higher than current/baseline diets. Multiple benefits for both health and the environment were reported in the majority (n = 315[76%]) of measurements. We identified consistent evidence of both positive health effects and reduced environmental footprints accruing from 'sustainable diets'. The notable exception of increased water use associated with 'sustainable diets' identifies that co-benefits are not universal and some trade-offs are likely. When carefully designed, evidence-based, and adapted to contextual factors, dietary change could play a pivotal role in climate change mitigation, sustainable food systems, and future population health.